2021
DOI: 10.1177/00031348211054567
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cholecystostomy Tubes versus Medical Management for Acute Cholecystitis

Abstract: Background Cholecystitis is one of the most common infections treated surgically in the United States. Surgical risk is prohibitive in some patients, leading to alternative therapeutic strategies, including medical management (antibiotics) with or without percutaneous cholecystostomy tube (PCT) drainage. Materials and methods Using the Healthcare Cost and Utilization Project (HCUP) National Readmission Database (NRD), we performed a retrospective review to compare medically managed patients with or without PCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Laparoscopic cholecystectomy is the treatment of choice for AC [ 12 , 13 ]. The surgical risk of the cholecystectomy itself is relatively low, but if the patient is unstable, percutaneous cholecystostomy can be performed, or surgery can be delayed [ 14 ]. For low-risk patients, early surgery is recommended, as a cholecystectomy can be safely performed within 48–72 h of disease onset, during the congestive or edematous phase.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy is the treatment of choice for AC [ 12 , 13 ]. The surgical risk of the cholecystectomy itself is relatively low, but if the patient is unstable, percutaneous cholecystostomy can be performed, or surgery can be delayed [ 14 ]. For low-risk patients, early surgery is recommended, as a cholecystectomy can be safely performed within 48–72 h of disease onset, during the congestive or edematous phase.…”
Section: Discussionmentioning
confidence: 99%
“…The results can hardly be compared [52][53][54][55][56][57][58][59][60][61]. In general, patients receiving PGBD have more comorbidities or critical illnesses than the ones allocated for surgery [54,62] or for conservative treatment [63], most probably contributing to the higher complication rates.…”
Section: Data Backgroundmentioning
confidence: 99%
“…Not included in the recommendations in the guidelines, antibiotics alone, simple (repeated) aspiration, and observation only are other treatment options [62,63,65,[68][69][70][71][72].…”
Section: Data Backgroundmentioning
confidence: 99%
“…It has been reported that 20% of patients admitted with biliary diseases have acute cholecystitis [1]. It is one of the most common complaints of all emergency department (ED) visits and occurs in 3-10% of patients with acute abdominal pain present in the ER [2].…”
Section: Introductionmentioning
confidence: 99%